RESEARCH OF TEXT AND CONTRIBUTION IN TEACHING JAPANESE - Nurhadi, Didik (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
This study aims to describe main problems of Japanese language text study, current text research and its application in Japanese language learning. Referring to the understanding of text as the largest and most comprehensive set of language study, the understanding of concepts and limitations in text study required for language learners, especially foreign languages learners, students should understand the concept and limitation of the text. The research method used descriptive qualitative research methods. The study results gained conclusion that text in Japanese language studies focused on study of text structure, especially discussion of text coherence. The views on this issue become a basis for understanding applied in teaching Japanese as a foreign language. This study focuses on discussion mentioned various research problems that can be raised and an example of text study research results applied with Japanese Language Text Structure Classification, Japanese Language Material Teaching, and contrastif language study